2010
DOI: 10.1098/rspb.2010.0972
|View full text |Cite
|
Sign up to set email alerts
|

Limited CD4+ T cell proliferation leads to preservation of CD4+ T cell counts in SIV-infected sooty mangabeys

Abstract: Human immunodeficiency virus (HIV) and simian immunodeficiency virus (SIV) infections result in chronic virus replication and progressive depletion of CD4þ T cells, leading to immunodeficiency and death. In contrast, 'natural hosts' of SIV experience persistent infection with high virus replication but no severe CD4þ T cell depletion, and remain AIDS-free. One important difference between pathogenic and non-pathogenic infections is the level of activation and proliferation of CD4þ T cells. We analysed the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
3
12
0
Order By: Relevance
“…As expected, both the fraction (33.97% Ϯ 2.64% versus 57.88% Ϯ 1.69%; P Ͻ 0.0001) (see ϩ T cells were significantly lower in SIV-infected than uninfected RMs. However, consistent with previous reports (9,32,34,35), the large majority of SIV-infected SMs maintained their fraction and number of CD4 ϩ T cells at levels similar to those found in uninfected animals (see Fig. S1C and S1D in the supplemental material).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…As expected, both the fraction (33.97% Ϯ 2.64% versus 57.88% Ϯ 1.69%; P Ͻ 0.0001) (see ϩ T cells were significantly lower in SIV-infected than uninfected RMs. However, consistent with previous reports (9,32,34,35), the large majority of SIV-infected SMs maintained their fraction and number of CD4 ϩ T cells at levels similar to those found in uninfected animals (see Fig. S1C and S1D in the supplemental material).…”
Section: Resultssupporting
confidence: 81%
“…These data thus suggest that in pathogenic SIV infection, increased proliferation of CD4 ϩ TCM cells fails to maintain the homeostasis of the overall CD4 ϩ T cell compartment. Of note, this finding lends support to a previously described model that a heightened level of CD4 ϩ T cell proliferation can result in decreased numbers of uninfected CD4 ϩ T cells (35). The situation is exactly the opposite in SIV-infected SMs, in which the fraction of CD4 ϩ Ki-67 ϩ TCM cells is not increased compared to that in uninfected animals and, in fact, correlates positively with the level of CD4 ϩ T cells.…”
Section: Cd4supporting
confidence: 70%
See 1 more Smart Citation
“…4 Additionally, low percentages of CD4 + Ki67 + cells have been linked to CD4 preservation in SM. 34 While activated and effector memory cells support high levels of virus replication, limited proliferation and CCR5 expression in central memory CD4…”
Section: Cd127mentioning
confidence: 99%
“…Furthermore, in contrast to the massive immune depletion that occurs in the gastrointestinal (GI) tract of non-natural hosts of SIV or HIV infection, natural NHP SIV hosts maintain GI epithelial integrity and exhibit a lack of microbial translocation that may in part account for minimal systemic immune activation [33,34]. Limiting the pool and/or proliferative capacity of target cells may also play a role in disease resistance, as demonstrated by studies in sooty mangabeys in which SIV replication was shown to be restricted to primarily short-lived activated CD4+ T-cells, which likely contributes to the preservation of central memory CD4+ T-cells [35,36]. A population of double negative (CD4-CD8-) T-cells capable of producing Th1, Th2 and Th17 cytokines have also been identified in sooty mangabeys, and are thought to compensate for CD4+ T-cell helper functions in SIV-infected animals [37].…”
Section: Old World Nhp Natural Hostsmentioning
confidence: 99%